2007
DOI: 10.1182/blood-2006-11-055186
|View full text |Cite
|
Sign up to set email alerts
|

Drug treatment is superior to allografting as first-line therapy in chronic myeloid leukemia

Abstract: Early allogeneic hematopoietic stem cell transplantation (HSCT) has been proposed as primary treatment modality for patients with chronic myeloid leukemia (CML). This concept has been challenged by transplantation mortality and improved drug therapy. In a randomized study, primary HSCT and best available drug treatment (IFN based) were compared in newly diagnosed chronic phase CML patients. Assignment to treatment strategy was by genetic randomization according to availability of a matched related donor. Evalu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
85
0
5

Year Published

2008
2008
2022
2022

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 135 publications
(96 citation statements)
references
References 21 publications
3
85
0
5
Order By: Relevance
“…However, a prospective randomized study was recently reported that compared outcomes in a cohort of early CP patients randomized to HSCT versus best available drug treatment (INF in combination with hydroxyurea) and demonstrated an improved OS for those receiving medication therapy despite higher rates of CCyR in the transplant population. 120 Recently, a subgroup analysis of the German CML-IV study demonstrated a 91% 3-year survival in those patients undergoing transplant after imatinib failure. 121 on the basis of expert opinion from the ELN, allogeneic transplant may be considered for those patients who have failed a second-line TKI, patients in AP-or BP-CML at the time of diagnosis or upon relapse or those with the T315I mutation.…”
Section: Sctmentioning
confidence: 99%
“…However, a prospective randomized study was recently reported that compared outcomes in a cohort of early CP patients randomized to HSCT versus best available drug treatment (INF in combination with hydroxyurea) and demonstrated an improved OS for those receiving medication therapy despite higher rates of CCyR in the transplant population. 120 Recently, a subgroup analysis of the German CML-IV study demonstrated a 91% 3-year survival in those patients undergoing transplant after imatinib failure. 121 on the basis of expert opinion from the ELN, allogeneic transplant may be considered for those patients who have failed a second-line TKI, patients in AP-or BP-CML at the time of diagnosis or upon relapse or those with the T315I mutation.…”
Section: Sctmentioning
confidence: 99%
“…The 10-year survival probability increased from 20 to 53% with previous usually interferon alpha (IFN)-based standard therapy (Hehlmann et al 2003(Hehlmann et al , 2007 to about 90% in the imatinib era (Bjorkholm et al 2011;Hehlmann et al 2011). Given the treatment success and approximately 6000 newly diagnosed patients per year in Europe (Hoffmann et al 2015) and 6600 in the US (Howlader et al 2015) maximizing adherence to promote optimal outcomes is crucial.…”
Section: Introductionmentioning
confidence: 99%
“…Chemotherapeutic agents and small molecule inhibitors or antibodies targeted to specific signaling pathways (often in combination) are most often used, 22,23 as they are in other forms of acute leukemic disease. [24][25][26][27][28] A monoclonal antibody that reduces circulating tumor cells could find clinical utility, e.g., as an adjuvant therapy in leukemia/lymphoma patients during acute disease. Alternatively, such an antibody might find use in a regimen for preventing tumor recurrence with patients in remission.…”
Section: Discussionmentioning
confidence: 99%